2014
DOI: 10.1242/jcs.161588
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin controls nectin recruitment into adherens junctions by remodeling the actin cytoskeleton

Abstract: BSTRACTThe mechanism that coordinates activities of different adhesion receptors is poorly understood. We investigated this mechanism by focusing on the nectin-2 and E-cadherin adherens junction receptors. We found that, cadherin was not required for the basic process of nectin junction formation because nectin-2 formed junctions in cadherin-deficient A431D cells. Formation of nectin-2 junctions in these cells, however, became regulated by cadherin as soon as E-cadherin was re-expressed. E-cadherin recruited n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…The size of cadherin cluster may increase as cadherin ectodomains organize into a two-dimensional (2D) lattice arrangement (Harrison et al 2011). Increased local concentration of a-catenin through cadherin clustering and multiple a-catenins associating with the same actin filament may promote clustering of the a-catenin actin-binding domains (Chen et al 2015) and actin bundling (Rimm et al 1995), hence further associating multiple cadherin clusters intracellularly through the actin network to form a mature junction. Vinculin has not been considered in this representation, although it plays a major role, because the interface of its interaction with a-catenin is only very poorly resolved at the ultrastructural level and because its open/closed conformational switch at adherens junctions is not yet well established.…”
Section: Historical Perspective a Few Misunderstandingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of cadherin cluster may increase as cadherin ectodomains organize into a two-dimensional (2D) lattice arrangement (Harrison et al 2011). Increased local concentration of a-catenin through cadherin clustering and multiple a-catenins associating with the same actin filament may promote clustering of the a-catenin actin-binding domains (Chen et al 2015) and actin bundling (Rimm et al 1995), hence further associating multiple cadherin clusters intracellularly through the actin network to form a mature junction. Vinculin has not been considered in this representation, although it plays a major role, because the interface of its interaction with a-catenin is only very poorly resolved at the ultrastructural level and because its open/closed conformational switch at adherens junctions is not yet well established.…”
Section: Historical Perspective a Few Misunderstandingsmentioning
confidence: 99%
“…Coupling these clusters with F-actin through an a-catenin actin-binding domain dramatically extends cluster lifetime and alleviates the dependence of their formation on the presence of the cis-binding interface. In ad-dition, the a-catenin actin-binding domain has been shown to cooperatively bind to F-actin (Buckley et al 2014;Hansen et al 2013), form clusters on F-actin (Chen et al 2015) and facilitates actin bundling (Rimm et al 1995). Thus, the cadherin extracellular region produces intercellular adhesion clusters through trans and cis inter-cadherin bonds, although the intracellular region connects these clusters to the cytoskeleton and may promote further clustering through a-catenin (Fig.…”
Section: Cadherin Micro-and Nanoclustering and F-actin Associationmentioning
confidence: 99%
“…Although both afadin and α-catenin are essential for the associations of nectins and cadherins, the underlying mechanism of how the nectin-afadin system is associated with the cadherincatenin system remains unknown [11,12]. Recent study reported that cadherins control nectin recruitment into AJs through actin clustering [17]. These observations suggest that both actin bundle formation and adhesion complex clustering mutually regulate cell-cell junction formation.…”
Section: Molecular Basis Of Cadherins and Nectins In Cellular Recognimentioning
confidence: 99%
“…E-cadherin is a transmembrane glycoprotein whose intracellular area can connect to microfilaments, intermediate filament proteins, and actin by catenins [20,21]. After forming a complex, E-cadherin is Banchored^to the cytoskeleton.…”
Section: E-cadherin Suppress Neurite Outgrowth In Ngf-stimulated Pc12mentioning
confidence: 99%
“…E-cadherin forms the key functional component of adherens junctions (AJs) between cells and is bound via a series of membrane proximal proteins to cytoskeletal actin [20]. AJs that connect cells can resist dissociating forces and transmit forces to adjacent cells, thereby making important contributions to the morphogenesis and homeostasis of tissues [13].…”
Section: Introductionmentioning
confidence: 99%